Integrated Proteomic and Metabolomic Analyses Provide Insights Into Acquisition of Embryogenic Ability in Agapanthus praecox - Yue, Jianhua; Dong, Yan; Liu, Songhu; Jia, Yanan; Li, Chaoxin; Wang, Zhiyong; Gong, Shoufu (Frontiers in Plant Science, 2022)
Somatic embryogenesis (SE) is an ideal model for plant cell totipotency. Transition from somatic cells to embryogenic cells is the key to SE. The poor frequency of embryogenic callus (EC) induction has limited the application of SE in many plants, such as Agapanthus praecox. We performed large-scale, quantitative proteomic and metabolomic analyses with different callus differentiation directions (SE and organogenesis) and stages (initial SE and repetitive SE) to better understand the morphological, physiological, and molecular characteristics of the acquisition of embryogenic ability in A. praecox. Integrated proteomic and metabolomic analyses suggested that callus differentiation direction was potentially regulated by pathways related to carbohydrate and energy metabolism (fatty acid metabolism, pyruvate metabolism, glycolysis/gluconeogenesis, pentose and glucuronate interconversions, starch and sucrose metabolism, galactose metabolism, carbon fixation pathways in prokaryotes, carbohydrate digestion and absorption, and fructose and mannose metabolism), chromatin accessibility and DNA methylation, reactive oxygen species responses and resistance (ascorbate and aldarate metabolism), and plant hormonal signaling. As a validation, we found that carbon source combination and plant hormone regulation in the culture medium significantly affected the acquisition of embryogenic ability, thereby inducing EC. Interestingly, plant hormonal signaling-related genes showed different expression patterns significantly when callus cultured with different carbon sources. Thus, our results suggested that energy supply and hormone signal transduction seemed to cooperatively contribute to the activation of embryogenic ability. Altogether, this study revealed valuable information regarding the molecular and biochemical changes that occurred during EC induction, and provided valuable foundation for comprehensive understanding of the mechanisms associated with SE and organogenesis in A. praecox.